PENGARUH CASH HOLDING, BONUS PLAN, DAN FIRM VALUE TERHADAP INCOME SMOOTHING - Samudra, Kelsa Surya; Wulandari, Rosita (Jurnal Riset Terapan Akuntansi, 2024)
This research aims to study how cash holding, bonus plan, and firm value affect income smoothing. The independent variables used are cash holding, bonus plan, and firm value. The dependent variable used in the research is income smoothing which is measured by a dummy variable. The research population is non-cyclical consumer sector companies listed on the IDX in 2018-2022. This research uses a sample of 27 companies selected using purposive sampling techniques, with a total of 135 data collected over five years. The analytical method used is logistic regression, and data processing is carried out using Eviews version 12 software. The data used is secondary data in the form of published annual reports. The results of research that has been carried out partially show that the cash holding and bonus plan variables have no effect on income smoothing. However, the firm value variable shows a positive influence on income smoothing. Simultaneously, cash holding, bonus plan, and firm value influence income smoothing.Keywords: bonus plan; cash holding; firm value; income smoothing.